A qualitative reflexive thematic analysis into the experiences of being identified with a BRCA1/2 gene alteration: "So many little, little traumas could have been avoided" - Nikolett Zsuzsanna Warner; AnnMarie Groarke (BMC, 2022)
Abstract Background BRCA1/2 alterations increase females' lifetime breast cancer risk to 40 - 90%, ovarian cancer to 10 - 60%, and males' lifetime prostate cancer risk to ~ 10 - 25%. Psychosocial issues such as heightened distress can, therefore, occur in this population. This study aimed to explore the subjective experiences and needs of the BRCA1/2 alteration population in navigating cancer risk reduction measures. Method This study aimed to explore the experiences and identify the needs of 18 BRCA1/2 alteration carriers, recruited through strategic sampling. A public and patient panel (N = 6) collaborated on study development. Data were analysed using reflexive thematic analysis. Results Two themes were identified: (i) Healthcare Services as a Burden to Navigate, and (ii) Burden Experienced Through Interactions with Healthcare Professionals. Results indicated uncertainty regarding care pathways, alongside a lack of relevant information. Participants felt unsupported by healthcare professionals, and as though healthcare professionals often perceive them as a burden. Conclusions These findings suggest that the quality of interactions in healthcare systems are of relevance to the BRCA1/2 alteration population, and that uncertainty surrounding access to services and information is prevalent. The establishment of specialist hereditary cancer clinics could reduce such burden.